Analysis and selection of skf bt2-8131 a roller bearing lubricant for the vertical roller mill at pt. solusi bangun indonesia tuban factory - Suhariyanto; Rusdiyana, Liza; Sampurno, Bambang; Hakim, M Lukman; Abimanyu, Abiyyu Abyan (Jurnal Nasional Aplikasi Mekatronika, Otomasi dan Robot Industri (AMORI), 2025)
In the industrial world, friction between machine elements such as bearings can affect the performance and service life of components, making lubrication systems based on tribology principles very important. This study analyzes the selection of lubricants for SKF BT2-8131 A roller bearings in a Vertical Roller Mill owned by PT. Solusi Bangun Indonesia, Tuban Factory, with the aim of determining a better lubricant than before and identifying the type of lubricant film formed. The research process involved collecting machine operational data and lubricant specifications, as well as calculating the kappa value and Streibeck curve to determine the type of lubricant layer, such as boundary, mixed, or full film lubrication. The results showed that Pertamina Masri RG 460 lubricant with a kappa value of 1.29 was selected because it had adequate technical performance and was more economical, although Mobil SHC 600 460 lubricant with a kappa value of 1.73 was also recommended if technical performance was the main priority. The results were validated by calculating the predicted bearing life to ensure optimal efficiency and performance.